Politicizing Literature and Literalizing Politics in Alobwed Epies the Death Certificate and Anyi-Kwe Armahs the Beautyful Ones are not Yet Born (London Journal of Research In Humanities and Social Sciences, 2026)
Volumes of literature and critical works have been written in an attempt to situate the place of politics in literature. Some postcolonial writers have argued vehement that it is practically impossible to write apolitical literature in the postcolonial world. This paper considers Alobwed ’Epie and Ayi kwei Armah as writers in “Postcolonial Politics”. Their novels are considered here as political pamphlets designed to castigate specific political regimes which have transformed the lives of the citizens into a perpetual nightmare. It equally examines the novels as those that expose some of the most gruesome and nauseating realities of postcolonial leadership politics. Furthermore, this paper sustains the argument that in the novels under study, the masses are projected as people who have been politically, economically and socially deceived, marginalized, oppressed, persecuted, enslaved, exploited and brutalized as a result of excessive greed, corruption, nepotism and tribalism. These ills are the major viruses that continue to deprive the pauperized masses from the benefits of independence as the transition from the colonial to the neo-colonial regimes was a mere change of political actors but the leadership tactics remained the same.From a Marxist and New Historicist theoretical paradigms, the analyses reveal that there is a thin line between the world of the novels and the social climate in which they resonate and adumbrate. Consequently, the novelists succeeds in transforming political realities into eternal truths of the human condition in postcolonial Africa. The analyses further stress that the novels offer synthesis of the people’s political experiences reconstructed in prosaic form. As such, the novelists consider the servant leadership and the moralization of political leadership as condition sino qua nons towards a free, fair and transparent society.